e-Learning transformation during the covid-19 pandemic among faculty members at princess nourah bint abdul rahman university - ALODAN, HAIFA (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT It seeks to shed light on the problems of the transition to e-learning during the Covid-19 pandemic among the collaborators of the Princess Nourah Bint Abdul Rahman University faculty, through a descriptive and analytical approach. The tool was represented with the help of a questionnaire organized by the researcher divided into 3 axes, concluding that organizational problems such as problems of slowness, download problems, conversation failure and their obstacles, have the need to articulate activities, criteria of evaluation and questions according to the specifications and tests of distance education. RESUMEN Se busca arrojar luz sobre los problemas de la transición al e-learning durante la pandemia de Covid-19 entre los colaboradores de la facultad de la Universidad Princess Nourah Bint Abdul Rahman, a traves de un enfoque descriptivo y analítico. La herramienta fue representada con la ayuda de un cuestionario organizado por el investigador dividido en 3 ejes, concluyendo que los problemas organizacionales como problemas netos de lentitud, problemas de descarga, falla de conversación y sus obstáculos, tienen la necesidad de articular actividades, criterios de evaluación y preguntas acordes con las especificaciones y pruebas de la educación a distancia.